Pregnancy outcome in rheumatic mitral stenosis patients with and without surgical correction: a prospective cohort study - Bahloul, Mustafa; Michael, Armia; Kandeel, Mansour Y.; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of the current study is to assess the maternal and fetal outcomes of pregnant females with and without surgically corrected mitral stenosis (MS). Methods: A cross sectional study was carried out at Assiut Women’s Health Hospital, Egypt between February 2016 and December 2016. All pregnant women diagnosed with rheumatic heart disease attending the antenatal care clinic were enrolled in the study. They were divided into two groups according to previous surgical correction of MS or not. All women were followed up during pregnancy till the end of puerperium. The primary outcome of the study was the difference in the rate of maternal cardiac complications during pregnancy between both groups. Results: The study included 48 patients (39%) with surgically corrected MS and 75 patients (61%) with uncorrected MS. All cardiac complications were significantly higher in the uncorrected MS group (p <0.05). No difference between both groups in the mode of delivery (p=0.52). Postpartum hemorrhage is more common with the corrected MS group than the uncorrected group (25% vs. 9.3% respectively, p=0.003), while the need for postpartum admission to ICU was significantly higher in the uncorrected group (p=0.006). The mean birth weight was higher in the corrected MS group (p=0.000). The percentage of stillbirths and the rate of admission to PCU was higher in the uncorrected MS group (p=0.003). Conclusions: Surgical correction of MS significantly improves the maternal and fetal outcomes of rheumatic heart pregnant females with MS.